The effect of crude fiber on pregnant sows’ and their piglets’ performance (ACTA AGRARIA KAPOSVARIENSIS, 2002)
The crude fiber content of the pregnant sows diets can influence the performance, primarily the reproductive performance of the sow. Feeding the pregnant sows according to their nutritional requirements can increase the number of stillborn pigs and weaned pigs. Fibrous feed components decrease the digestibility and the absorption of the other nutrients. However, a given amount of crude fiber is required in the pregnant sows’ diets because of their special physiological role. Three different feeds (control, basal diet plus fermentable corn silage and basal diet plus non-fermentable wheat straw) were fed with pregnant sows in two repetitions in order to determine the crude fiber requirement of the sows during this period. The number of stillborn and number of weaned piglets, as well as the feed-intake (including the energy and protein intake) during lactation increased in response to the fiber supplementation. These findings confirm the beneficial effects of crude fiber addition by supplementing the pregnant sows’ ratios with corn silage or wheat straw.